Reading Shaver's Creek : Ecological Reflections from an Appalachian Forest - Weidensaul, Scott; Warren, Julianne Lutz; Taylor, David; Marshall-McKelvey, Jacy; Marshall, Ian; Marshall, Ian; Mahan, Carolyn; Lane, John; Inglesby, Hannah; Gessner, David; Fallon, Katie; Davis, Todd; et al. (Book collections on Project MUSE., 2021)
What does it mean to know a place? What might we learn about the world by returning to the same place year after year? What would a long-term record of such visits tell us about change and permanence and our place in the natural world? This collection explores these and related questions through a series of reflective essays and poems on Pennsylvania's Shaver's Creek landscape from the past decade.Collected as part of The Ecological Reflections Project--a century-long effort to observe and document changes to the natural world in the central Pennsylvanian portion of the Appalachian Forest--these pieces show how knowledge of a place comes from the information and perceptions we gather from different perspectives over time. They include Marcia Bonta's keen observations about how humans knowingly and unknowingly affect the landscape; Scott Weidensaul's view of the forest as a battlefield; and Katie Fallon describing the sounds of human and nonhuman life along a trail. Together, these selections create a place-based portrait of a vivid ecosystem during the first decade of the twenty-first century.Featuring contributions by nationally known nature writers and local experts, Reading Shaver's Creek is a unique, complex depiction of the central Pennsylvania landscape and its ecology. We know the land and creatures of places such as Shaver's Creek are bound to change throughout the century. This book is the first step to documenting how.In addition to the editor, contributors to this volume are Marcia Bonta, Michael P. Branch, Todd Davis, Katie Fallon, David Gessner, Hannah Inglesby, John Lane, Carolyn Mahan, Jacy Marshall-McKelvey, Steven Rubin, David Taylor, Julianne Lutz Warren, and Scott Weidensaul.